2012
DOI: 10.1515/jpem-2012-0025
|View full text |Cite
|
Sign up to set email alerts
|

In congenital hypothyroidism, an initial L-thyroxine dose of 10–12 μg/kg/day is sufficient and sometimes excessive based on thyroid tests 1 month later

Abstract: An initial L-T4 dose of 10-11.9 μg/kg for TSH>100 μIU/L and 8-10 μg/kg for TSH<100 μIU/L at diagnosis met and often exceeded the target thyroid levels at 1 month. More frequent overtreatment was seen when >12 μg/kg was given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This is consistent with the findings of another study that reported more frequent OT 1 month after starting therapy when >12 mcg/kg was given (4). These authors suggested that initial LT4 doses of 10 to 11.9 mcg/kg for infants with a TSH >100 mcU/L and 8 to 10 mcg/kg for those with a TSH <100 mcU/mL are sufficient.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the findings of another study that reported more frequent OT 1 month after starting therapy when >12 mcg/kg was given (4). These authors suggested that initial LT4 doses of 10 to 11.9 mcg/kg for infants with a TSH >100 mcU/L and 8 to 10 mcg/kg for those with a TSH <100 mcU/mL are sufficient.…”
Section: Discussionsupporting
confidence: 92%
“…In children with congenital hypothyroidism (CH), early identification and treatment with high-dose levothyroxine (LT4) at 10 to 15 mcg/kg daily has been shown to rapidly normalize thyroid-stimulating hormone (TSH) levels and improve neurodevelopmental outcomes (1,2). However, the risk of inducing supraphysiologic thyroxine levels increases with higher initial doses of LT4 (3,4). Several studies have suggested that this might also be harmful to the developing brain, and episodes of over-treatment (OT) have been linked to a difficult temperament in infancy, as well as lowered intellectual functioning and decreased attention span later in childhood (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we evaluated the effects of initial L-thyroxine doses on patients with CH and found that the rate of overtreatment at the first month is significantly higher in the high-dose group. Similarly, Vaidyanathan et al (6) reported an overtreatment rate of patients who received 12-15 μg/kg/day of LT4 as an initial dose, which was higher at the first month compared with groups receiving 10-11.99 μg/kg/day and 6-9.9 μg/kg/day at month 1 (75%, 55% and 37.5%, respectively).…”
Section: Discussionmentioning
confidence: 86%
“…In the study performed by Vaidyanathan et al in 55 patients (6), they revealed that infants with a TSH level of 100 μIU/L or higher received a mean LT4 dose of 12.6 μg/kg/day and had higher rates (71%) of overtreatment. They also reported that a lower dose of LT4 (8-10 μg/kg/day) could be sufficient in infants with less severe CH (TSH: 20-100 μIU/L).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation